Konstruksi Naratif Kampanye Bye Bye Plastic Bag Surabaya: Melacak Makna dalam Komunikasi Lingkungan untuk Menggugah Sikap Permasalahan terhadap Plastik Sekali Pakai - Obelix Son (Journal of Management and Bussines (JOMB), 2024)
This research the "Bye Bye Plastic Bag Surabaya" campaign and the messages contained in it. The research method used is a descriptive qualitative approach, with data collection techniques through participant observation, in-depth interviews with relevant stakeholders, and content analysis of campaign materials and public responses. The research results showed that the campaign was effective in increasing Surabaya people's awareness of the single-use plastic problem and in changing their behavior towards more sustainable use. The conclusion is that effective communication, using strong and emotional narratives, can be a powerful tool in driving social change related to the use of single-use plastic. Managing single-use plastic waste requires collaboration between government, industry and society to create sustainable solutions to reduce its negative impact on the environment and human health. Keywords: Environment, Narrative Construction, Plastic